Pendampingan Sertifikasi Halal Oleh Penyuluh Agama Sebagai Strategi Penguatan Ekonomi UMKM Di Indonesia - Dewi, Tika; Sa'adah, Nailus (Jurnal Landraad, 2024)
The facilitation of halal certification by religious counselors serves as a strategic approach to strengthening the economy of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Halal certification not only enhances consumer trust but also opens opportunities for MSMEs to access broader markets, both domestically and internationally. This study aims to analyze the role of religious counselors in assisting MSMEs throughout the halal certification process and its impact on improving business capacity and economic competitiveness. A descriptive qualitative method was employed, with data collected through interviews, observations, and literature review. The results show that the active involvement of religious counselors helps MSMEs understand the procedures and benefits of halal certification while fostering a more sustainable business ecosystem. With such support, MSME operators can enhance product quality and meet halal standards, thereby increasing their market competitiveness. The study concludes by highlighting the importance of synergy between religious counselors, certification bodies, and the government to effectively and sustainably strengthen the MSME economy through halal certification.